Abundant Exact Explicit Solutions to a Modified cKdV Equation (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we construct abundant exact explicit solutions toa modified cKdV equation by employing the three forms of $(ω/g)$-expansionmethod, i.e., $(g' /g^2)$-expansion method, $(g' /g)$-expansion method and $(g')$-expansion method. The solutions obtained are under different constraint conditions and are in the form of hyperbolic, trigonometric and rational functions,respectively, including kink (antikink) wave solutions, singular wave solutionsand periodic singular wave solutions which have potential applications in physical science and engineering.
Keywords: Modified cKdV equation; Exact explicit solutions; $(ω/g)$-expansion method; $(g'/g^2)$-expansion method; $(g'/g)$-expansion method; $(g')$-expansion method.